Transradial approach for coronary interventions - Brito,José Carlos (2001)
OBJECTIVE: To assess the feasibility and safety of coronary interventions performed through the radial artery. METHODS: We studied 103 patients with ages from 38 to 86 years (57±8.7), 90 (87%) males, and: radial pulse with a good amplitude, presence of ulnar pulse, a good collateral flow through the palmar arch assessed with the Allen's test. RESULTS: The vascular approach was obtained in 97 (94%) patients, 88 (91%) treated electively and 9 (9%) during acute myocardial infarction, for primary angioplasty; 56 (64%) unstable angina; 22 (25%) stable angina; 10 (11%) were asymptomatic, 6 referred for recanalization of chronic occlusion and 4 silent ischemia in the first week after acute myocardial infarction. We approached 107 arteries: anterior descending artery, 49 (46%); right coronary artery, 27 (25%); circumflex artery, 25 (23%); diagonal artery, 6 (6%); and 2 saphenous vein bypass grafts. We treated 129 lesions: 80 (62%) B2 type; 23 (18%) B1 type; 17 (13%) C type; and 9 (7%). A type. There were 70 stents , and 59 balloon angioplasties performed. Thirty-two (33%) patients used GP IIb/IIIa inhibitors. The mean duration of the elective procedure was 42.3±12.8 min. Success, correct stent deployment and residual lesion <20%, was reached in 100% of the lesions treated with stent implantation; arterial dilation with residual lesion <50% was obtained in 96% of the lesions treated with transluminal coronary angioplasty (TCA). Complications, were: 1 (1.0%) non-Q-wave acute myocardial infarction; 2 (2%) hematomas in the forearm; and 2 losses of radial pulse. CONCLUSION: Radial artery aproach is practical and safe for percutaneous coronary interventions there was a low incidence of complications.